Efficacy and Cost Economics of Bio-Pesticides and Botanical Extracts Against Cabbage Butterly Pieris Brassicae Nepalensis Doubleday in Cauliflower Crop in Ilam, Nepal: Bio-Pesticides for Cabbage Butterfly Control - Subedi, Anupa; Tiwari, Sundar; Mishra, Niraj (SAARC Journal of Agriculture, 2025)
A field experiment was conducted to compare the efficacy and profitability of using bio-pesticides and locally available botanical extracts for the management of cabbage butterfly Pieris Brassicae Nepalensis Doubleday for cauliflower production. The management study was established in a farmer’s field in Barhabasti, Ilam, Nepal. Eight different types of management treatments were deployed in a randomized complete block design (RCBD) with three replications. The treatments were i) Bacillus thuringensis var kurstaki (2 gm /lt) ii) Metarhizium Anisopliae (2.5 ml /lit) iii) Beauveria Bassiana (3 ml /lit) iv) Acorus calamus (1:5) v) Lantana camara (1:5) vi) Neem oil (1.5 ml /lt) vii) Cow urine (1:4) viii) Control. Results showed that bio-pesticides and botanical extracts were significantly superior over control. L. camara treated plots contained the lowest larval population compared to all other treatments. The order of effectiveness of the treatments based on the population reduction was L. camara > A. indica > A. calamus > Cow urine > M. Anisopliae > B. thuringiensis > B. Bassiana > control. The above treatments were also safe for natural enemies since there was a non-significant mortality effect of bio-pesticides on natural enemies. The highest benefit-cost ratio (2.36) was recorded in neem oil-treated plots that were superior to all other treatments. To summarize, this study can help to develop an IPM protocol for the sustainable management of cabbage butterflies in crucifer fields. SAARC J. Agric., 22(2): 127-138 (2024)